Knowledge and quality as the factors of the business operations and competitiveness promotion - research results from Serbia - Cvjetkovic, Milena (Industrija, 2015)
The paper deals with the analysis of knowledge and quality as key factors of the promotion of business operations and competitiveness promotion. The objective of this paper is to establish the relations between the quality and the level of business operation and competitiveness, and the relations between the investment in knowledge, training and professional development and the promotion of business operations quality. The paper presents the research conducted among the company managers in Serbia, where their attitudes and opinions were used for assessing the level of business operations and competitiveness, the company’s readiness to invest in knowledge, training and professional development and quality promotion. The correlation analysis established the importance of the impacts of the given variables, where it was ascertained that promotion of the quality aspects has the greatest significance for the improvement of the competitive capacities of the Serbian companies. The importance of the research is evidenced in the results that can serve to Serbian company managers as the guidelines for the promotion of the business operations and competitiveness promotion.